Implementasi Akuntansi Digital dalam Pemerintahan: Tantangan dan Peluang (Studi Kasus Kabupaten Grobogan) - Amin Sadiqin; Buyung Cahya Perdana; Rizki Arvita (PUTRA JAWA PUBLISHER, 2024)
The application of digital accounting in government has become an important concern in efforts to increase efficiency, transparency and accountability in regional financial management. This study aims to analyze the implementation of digital accounting in the Grobogan Regency Government, as well as identifying the challenges and opportunities faced in this process. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observation and documentation. The research results show that the implementation of digital accounting in Grobogan Regency has provided significant benefits, including increased speed in financial reporting and ease of data access. However, the challenges faced include limited technological infrastructure, resistance to change, and lack of human resource competence. On the other hand, opportunities arising from this implementation include improving the quality of decision making, saving operational costs, and increasing community participation in budget oversight. In conclusion, despite various challenges, the potential benefits of digital accounting in government are enormous, especially in supporting transparency and efficiency in regional financial management.